Digital Maturity of Pre-service Mathematics Teacher on Geometry Learning - Arif Abdul Haqq; Isti Hidayah; Isnarto Isnarto; Bambang Eko Susilo (International Conference on Science, Education, and Technology, 2022)
Digital transformation is changing teacher competencies that students need to succeed. It is increasingly important for teachers to develop their digital maturity in this context proactively. The emerging research on teacher digital maturity development has largely ignored the possible role of teachers' perceptions of large-scale changes in mathematics teaching using technology, especially in geometry learning. Several studies have explored digital video technology in geometry learning as a supporting tool for teachers' digital maturity in mathematics teacher education. Previously, usually limited visibility in teaching to the production of static images and film clips of educational orientation, then with the advent of dynamic geometric systems, the pedagogical community gained movement as a new publicly available means of teaching mathematics of teacher digital maturity in geometry learning. We did the survey using keywords related to geometry learning and digital technology. We have surveyed several pre-service Mathematics Teachers on geometry learning. The analyzed papers have provided insight into maturity model dimensions were extracted and consolidated into a maturity model framework. The consolidated maturity model framework consisted of five stages: initial, managed, defined, predictable, and optimizing. The results show core competencies in digital maturity level, namely integrating digital technology in teaching processes (optimizing level), adjusting and applying different teaching methods (optimizing level), developing a standard model for digital teaching abilities (optimizing level), establishing effective assessment items and models for assessing digital teaching abilities (predictable level), and setting paradigms for outstanding teaching abilities (predictable level).